Influence of Renewable Fuels and Nanoparticles Additives on Engine Performance and Soot Nanoparticles Characteristics - Mohammed A. Fayad; Azher M Abed; Salman H Omran; Alaa Abdulhady Jaber; Amerah A Radhi; Hayder A Dhahad; Miqdam T Chaichan; Talal Yusaf (International Journal of Renewable Energy Development, 2022)
The fuel combustion in diesel engines can be improved by adding nanomaterials to the fuel which result in an reduction in pollutant emissions and enhance the quality of fuel combustion. The engine performance and soot nanoparticles characteristics were evaluated in this study with adding nanoparticles of copper oxide (CuO2) to the rapeseed methyl ester (RME) and diesel under variable engine speeds. The addition of CuO2 to the RME significantly improve brake thermal efficiency (BTE) and decline the brake specific fuel consumption (BSFC) by 23.6% and 7.6%, respectively, compared to the neat RME and diesel fuel. The inclusion CuO2 nanoparticles into the RME and diesel led to decrease the concentration and number of particulate matter (PM)by 33% and 17% in comparison with neat RME and diesel without nano additives, respectively. Moreover, PM is significantly decreased by 31.5% during the RME combustion in comparison with neat RME and diesel under various engine speeds. It was also obtained that the number of emitted particles (npo) reduced by 23.5% with adding nanoparticles to the RME in comparison with diesel, while the diameter of soot nanoparticles (dpo) increased by 8.6% in comparison with diesel. Furthermore, the addition CuO2 to the RME decreased the size and number of particles more than to the diesel fuel.